2001
DOI: 10.1103/physrevlett.87.106105
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Observation of an Atom-Sized Gold Wire by Phase Electron Microscopy

Abstract: A single-atom-sized gold wire was successfully observed in real time by a newly developed defocus-image modulation processing electron microscope. Because of phase retrieval processing with spherical aberration correction, the single-atom strand wire was observed with high contrast and without contrast blurring. By carefully looking at the atomic distance, the contrast, and the dynamic behavior of the wire, we recognized that there are two stages of the wire. In the first stage the wire maintained the atomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 9 publications
8
69
0
Order By: Relevance
“…Such chains are observed in break junction experiments when pulling apart metallic wires of Au, Pt or Ir [26][27][28][29][30] . Relativistic effects taking place in these metals strengthen the interatomic bonds between the low-coordinated atoms in the atomic constriction 28,31 .…”
Section: Main Textmentioning
confidence: 96%
“…Such chains are observed in break junction experiments when pulling apart metallic wires of Au, Pt or Ir [26][27][28][29][30] . Relativistic effects taking place in these metals strengthen the interatomic bonds between the low-coordinated atoms in the atomic constriction 28,31 .…”
Section: Main Textmentioning
confidence: 96%
“…24,25 It was demonstrated that in situ transmission electron microscopy ͑TEM͒ had an atomistic spatial resolution for deformation of nanocontacts of metals and isolators. [27][28][29][30][31][32][33][34][35][36][37] In particular, the stress-strain relation for nanometer-sized structures was directly observed by in situ TEM combined with sub-nanoNewton force measurement systems. 33,34,37 Synthesis and electrical properties of silicon ͑Si͒ contacts and wires have been extensively studied on nanometer scales.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanowires have recently attracted a great deal of attention due to their unusual properties and relative simplicity of fabrication. Most studied systems both experimentally [1][2][3][4][5][6][7] and theoretically [8][9][10][11][12][13][14][15][16] are free standing gold nanowires, which exhibit a quantized conductance at stretching and have peculiar structural properties. Unsupported and supported wires of Cu, Pd, Pt, Ag and Au have also been studied theoretically by means of ab initio and molecular dynamics methods [14], [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%